African Continental Free Trade Area: Is there a trade potential for Côte d'Ivoire? - Doukouré Charles Fe (Cogent Economics & Finance, 2021)
Many studies present the African Continental Free Trade Area (AfCFTA) as one of Africa's most new trade issues. Previous assessments show that this AfCFTA will catalyze Intra African trade. The cumulative impact on Côte d'Ivoire's exports in the long term is positive for other African countries without indicating potential partners. This study seeks to identify a potential partner to help policymakers to map out a better strategy. We use exports data from 2001 to 2016 on 45 African countries, and we compute an index to assess the gap. When asked if there are potential customers on the continent for Côte d'Ivoire from the perspective of the AfCFTA, it appears that yes. The results reveal great trade potentials for Côte d'Ivoire in Africa, at least in 25 countries. Among them, there are 8 Economic Community of West African States (ECOWAS) countries.
Keywords: F02; F15; O40; 330; Free trade agreements; trade policy; trade potential